Informetrics and discourse analysis applied to scientific production in Data Science and Information Science - Martínez Musiño, Celso (2021)
Objective. To research scientific production at the thematic intersection of Data Science (DS) and Information Science (IS). Method. Informetric, descriptive study, and of first incursion, in the analysis of the written discourse of the academic texts included in the Web of Science (WoS), period 1900 to November 6, 2020, and coverage in the databases: SCI-Expanded, SSCI, A & HCI, ESCI, CPCI-S, CPCI-SSH, BKCI-S and BKCI-SSH. Results. 49 documents represented in 38 articles, 7 conference memoires, 2 book chapters and 2 editorial materials were retrieved and analyzed. The set of investigations that deal with the subject of DS and IS added 128 citations, 2.6 citations per document and H index: 7. Discussion. Conceptually, it was found that for DS and IS their origin is the “data” and that both disciplines are predominantly practical. In those investigations with greater visibility there are more than an author. DS and IS are recent areas of knowledge in which information technologies are indispensable for the analysis of large amounts of data and information. Conclusions. DS and IS have an intra- and multi and transdisciplinary character and they are characterized by the use of information technologies for the analysis of large amounts of data and information.